Fecal incontinence and constipation in children case studies - Levitt, Marc A. (Marc Aaron), 1967-; Choueiki, Julie; Nash, Onnalisa (Boca Raton : CRC Press, 2019)
This book focuses on the management of children with fecal incontinence and constipation. Despite accurate anatomic reconstruction, many children still suffer from a variety of functional bowel problems. These include not only children with congenital anatomic problems such as anorectal malformations and Hirschsprung disease, but also includes the huge population of children who suffer from constipation, with or without soiling, and a large spinal population (spina bifida) who have bowel problems.
23. A patient with severe functional constipation who has failed laxative treatment and both rectal and antegrade enemas24. A patient who has recurrent constipation and soiling following colonic resection; 25. A young adult with intractable constipation and diffuse colonic dysmotility; 26. A young adult with pelvic floor dyssynergia; 27. A patient with severe constipation and a behavioral disorder; 28. A young adult with incontinence after a low anterior resection; 29. Two adults with incontinence after childbirth
OCLC-licensed vendor bibliographic record.
Keywords: Fecal incontinence in children -- Treatment; Constipation in children -- Treatment; MEDICAL / General; MEDICAL / Gastroenterology; MEDICAL / Surgery / General